Sustainable Education, Emotional Intelligence and Mother–Child Reading Competencies within Multiple Mediation Models - Jiménez-Pérez, Elena del Pilar; Vicente - Yagüe Jara, Mª Isabel; Gutiérrez-Fresneda, Raúl; García-Guirao, Pedro (IOAP-MPDI, 2021)
The influence of the family on the education of children is indisputable, and the mother plays a fundamental role as a direct influence on the educational process of children, especially on their reading competence. Systematically, the role of education has been delegated to the teacher when, even in academic aspects, the values of a society influence the education of the new generations. A sustainable society goes through a sustainable education, instilling values from a well-developed emotional intelligence. The objective of this study is to establish for first time the existence of relationships among reading habits, sex, and mother′s emotional intelligence regarding the reading comprehension of children. Participants included 521 adolescent baccalaureates aged between 16 and 17 years old, who attended three public baccalaureate schools in the province of Málaga and four public high schools in the province of Granada, all located in areas of medium socio-cultural context. Mediation and factorial analysis of covariance (ANCOVA) analyses were performed. The results show that girls with higher emotional intelligence and whose mothers have higher reading habits obtain higher reading competence.
Keywords: Educación; Reading competence; Emotional intelligence; Baccalaureate; Mediation analysis; Factorial ANCOVA